Primary ciliary dyskinesia: current state of the art. Issue 12 (18th July 2007) - Bush, Andrew; Chodhari, Rahul; Collins, Nicola; Copeland, Fiona; Hall, Pippa; Harcourt, Jonny; Hariri, Mohamed; Hogg, Claire; Lucas, Jane; Mitchison, Hannah M; O'Callaghan, Christopher; Phillips, Gill
Abstract : Primary ciliary dyskinesia (PCD) is usually inherited as an autosomal recessive disorder and presents with upper and lower respiratory tract infection, and mirror image arrangement in around 50% of cases. Cilia dysfunction is also implicated in a wider spectrum of disease, including polycystic liver and kidney disease, central nervous system problems including retinopathy and hydrocephalus, and biliary atresia. Cilia are complex structures, containing more than 250 proteins; recent studies have begun to locate PCD genes scattered throughout the genome. Screening tests for PCD include nasal nitric oxide and in vivo tests of ciliary motility such as the saccharin test. Specific diagnosis requires examination of cilia by light and electron microscopy, with epithelial culture in doubtful cases. This is only available in supra-regional centres, recently centrally funded by the National Commissioning Group. Treatment is not evidence based and recommendations are largely extrapolated from cystic fibrosis and other suppurative lung diseases.